Energy, tourism, finance, and resource depletion: panel data analysis. Issue 11 (2nd December 2018) - Bhuiyan, Miraj Ahmed; Zaman, Khalid; Shoukry, Alaa Mohamd; Gani, Showkat; Sharkawy, Mohamed A.; Sasmoko,; Khan, Aqeel; Ahmad, Adnan; Hishan, Sanil S.
ABSTRACT: This study examines the dynamic linkages between alternative and nuclear energy consumption, tourism receipts, bank-specific factors, and environment and resource factors in a heterogeneous panel of countries for the period 1995–2016. The study also addresses the United Nations sustainable development agenda under a resource conservation framework across countries. A two-step differenced Generalized Method of Moments (GMM) estimator is employed for robust inferences. The results show that bank-specific factors substantially reduce resource depletion, whereas international tourism increases energy resource depletion and carbon emissions across countries. Nuclear energy consumption reduces resource depletion, whereas industrial value added increases resource depletion and carbon emissions; thus, it is imperative to devise strong policies for sustainable production across countries. The results of panel causality tests confirm different causality patterns among the studied variables. The study concludes that an environmental and resource conservation process needs sustainable policy instruments, including cleaner production techniques, renewable energy sources, and sustainable production and consumption to achieve green growth.